Laser microdissection system applied in improving FT-TIMS technique - Chen, Yan; Xu, Chang-Kun; Zhao, Yong-Gang; Guo, Shi-Lun; Li, Li-Li; Chang, Zhi-Yuan; Liu, Guo-Rong (Perspectives in science, 2019)
A laser microdissection system was used for isolating fission track stars to improve the cutting efficiency in the FT-TIMS particle analytical technique. The background interference of track detectors to determine isotopic ratios was studied. Several swipe samples were successfully measured for particle analysis by FT-TIMS. The results show that the laser microdissection system could effectively improve the ability of FT-TIMS particle analytical technique.